A reduced graphene oxide–NiO composite electrode with a high and stable capacitance. Issue 3 (17th January 2018) - Sun, Xiaoming; Lu, Hao; Liu, Peng; Rufford, Thomas E.; Gaddam, Rohit R.; Fan, Xin; Zhao, X. S.
Abstract : Thermal decomposition of Ni(acac)2 leads to in situ formation of NiO sandwiched between expanded graphite oxide layers, and this material displays good electrocapacitive properties. Abstract : We report a vacuum-thermal strategy for the preparation of a composite electrode material consisting of reduced graphene oxide and nickel oxide nanoparticles, which displays interesting electrocapacitive properties. Graphene oxide thermally expands in a vacuum and simultaneously nickel(ii ) acetylacetonate decomposes to form NiO nanoparticles between graphene layers. This method not only allows the uniform dispersion of NiO nanoparticles between graphene layers but also enables simultaneous reduction of graphene oxide. The structural and electrochemical advantages of both reduced graphene oxide and nanoscale NiO particles are maintained. The reduced graphene oxide–NiO composite exhibits a specific capacitance of 880 F g −1 at a current density of 1 A g −1 in 6 M KOH and a 93.1% retention of initial capacitance after 5000 cycles at 5 A g −1 .